1998
DOI: 10.1038/sj.bjp.0702130
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine administration stimulates the in vivo N‐methyl‐D‐aspartate receptor/nitric oxide/cyclic GMP pathway in rat hippocampus through glutamate release

Abstract: 1 The in vivo e ects of nicotine on the nitric oxide (NO) synthase/cyclic GMP pathway of the adult rat hippocampus have been investigated by monitoring the levels of extracellular cyclic GMP during microdialysis in conscious unrestrained animals. 2 Intraperitoneal (i.p.) administration of nicotine caused elevation of cyclic GMP levels which was prevented by mecamylamine. The e ect of nicotine was abolished by local infusion of the NO synthase inhibitor N G -nitro-L-arginine (L-NOARG) or by the soluble guanylyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 50 publications
0
43
0
Order By: Relevance
“…Changes in intracellular calcium probably represent an important initial event because nAChRs flux calcium and nAChR-evoked function is calcium dependent (O'Neill et al, 2002;Dajas-Bailador and Wonnacott, 2004;Quik, 2004;Wonnacott et al, 2005). Diverse downstream pathways and processes, such as phosphorylation, may be activated to lead to alterations in caspases, kinases, CREB (cAMP response element-binding protein), apoptotic signaling, the nitric oxide/cGMP pathway, and others (Fedele et al, 1998;Garrido et al, 2001;Brunzell et al, 2003;Mai et al, 2003;Jin et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in intracellular calcium probably represent an important initial event because nAChRs flux calcium and nAChR-evoked function is calcium dependent (O'Neill et al, 2002;Dajas-Bailador and Wonnacott, 2004;Quik, 2004;Wonnacott et al, 2005). Diverse downstream pathways and processes, such as phosphorylation, may be activated to lead to alterations in caspases, kinases, CREB (cAMP response element-binding protein), apoptotic signaling, the nitric oxide/cGMP pathway, and others (Fedele et al, 1998;Garrido et al, 2001;Brunzell et al, 2003;Mai et al, 2003;Jin et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…‫,ء‬ p Ͻ 0.05 or ‫,ءء‬ p Ͻ 0.01 compared with L-NAME (30)/Sal control group; #, p Ͻ 0.05 compared with KRB/Nic (0.065) treatment group; $, p Ͻ 0.05 compared with L-NAME (30)/Nic (0.065) group (n ϭ 4 -5 rats per cohort). tors and the subsequent activation of NMDA receptors (Fedele et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The records were later analyzed off-line by a person who was not familiar to the experiments. Dopamine-related behaviors, including sniffing, rearing, and locomotion, were distinguished (Fedele et al, 1998).…”
Section: Dopamine-related Behaviors Evaluationmentioning
confidence: 99%
“…This data further indicated that the effects of saffron extract and safranal may at least partially mediate in the CNS. Dopamine-related behaviors have been postulated to be changed during stress (Fedele et al, 1998). These changes are the manifestations of the effects of CRF, polyopiomelanocortin (POMC), and corticosterone released during stress from the hypothalamus, pituitary, and adrenal gland, respectively (Koob, 2008).…”
Section: Behavior Groupsmentioning
confidence: 99%